Analisis Penerapan Metode MOORA dan WASPAS dalam Keputusan Pengajuan Kredit Pemilikan Rumah (KPR) - Rizka Tri Alinse; Venny Novita Sari; Achmad Fikri Sallaby (Universitas Budi Darma, 2023)
To fulfill the necessities of life, humans need a place to shelter from the hot sun and the dark of the night even if it rains, the role of residence is very important. Not only that, the house can also be a place for gathering and carrying out family activities such as carrying out daily activities and communicating with each other. A house is an asset whose price is not cheap, so not a few people buy a house by credit. Therefore, the bank created a mortgage program to make it easier for people with limited economic conditions. Mortgages are made with payments in installments so it is likely that the bank will lose if the mortgage is given to the wrong person. So we need a system that facilitates the bank in making a decision. The Decision Making System (DSS) can be carried out using several methods such as MOORA, MOOSRA, WASPAS, TOPSIS, PSI, VIKOR, WP, SAW and others. In this study, the method used in determining the recipient of a Home Ownership Loan is the MOORA and WASPAS methods. These two methods will be applied separately based on existing criteria and alternatives. The final result after applying this method is that the best alternative is obtained by A7 with a Qi value of -0.04131 (MOORA method). Likewise with the application of WASPAS, the highest value was obtained for alternative A7 with a Qi value of 2.91829.